«Qualcosa che non ho mai dimenticato»: Fortini lettore di Virgilio - Gigliotti, Maria Teresa (L’ospite ingrato, 2024)
The article analyses some Virgilian memories found in the poetic work of Franco Fortini, which act both at a para-textual level and at a deeper level, involving the structure of some compositions. The analysis uses the mechanisms of allusive art, which is based on the agreement between author and reader; it also highlights the vitality of Latin tradition in the poetry of Fortini. The references to famous Virgil’s verses, finally, can be found in the translation of John Milton’s Lycidas, included in the Ladro di ciliege e altre versioni di poesia (1982), an evidence of the intertextuality of the poem.